MAKNA AL-NABĪ AL-UMMĪ PERSPEKTIF MUFASIR INDONESIA : (Penafsiran Bisri Mustofa dan Tim Lajnah Pentashihan Mushaf Al-Qur’an RI terhadap QS. Al-‘Arāf/7:157-158) - Panggih Widodo; Achmad Abubakar; Sohrah; Ahmad Dani (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
This study discusses the interpretation of the meaning of al-nabī al-ummī in QS al-A'rāf/7: 157-158 according to Bisri Mustofa and the Tim Lajnah Pentashihan Mushaf Al-Qur’an RI and is a literature study using primary and secondary data. The result of the research is that al-nabī al-ummī which is attributed to the Prophet Muhammad found in QS al-A'rāf/7: 157-158. Bisri Mustofa interpreted that the Prophet Muhammad could not read and write and also meant that he was clean from sin. Meanwhile, the Tim Lajnah Pentashihan Mushaf Al-Qur’an RI interpreted that the Prophet Muhammad not good at reading and writing. There are several similarities and differences in the interpretation of each of these figures in terms of the diversity of meanings of the sentence al-nabī al-ummī, the attribution of these characteristics to him, and the level of ability of the Prophet Muhammad in terms of reading and writing. The purpose of this research is to find out the interpretation of some Indonesian interpreters about the meaning of al-nabī al-ummī.